2015
DOI: 10.5603/aa.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations of symptoms of the chronic venous disease among primary health care patients in Poland

Abstract: The presented results were collected in the context of the PHLEBOS-2 research (multi-centre epidemiological study of patients suffering from chronic venous disease) carried out under the scientific grant of LEKAM Company with limited liability in the years 2011-2012. Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…De acordo com a Scottish Intercollegiate Guidelines Network, as Úlceras Venosas também denominada úlcera de estase ou varicosa, são as lesões mais graves da Síndrome da Insuficiência Venosa Crônica dos membros inferiores. A Úlcera Venosa é um problema de saúde pública por demandar cuidados contínuos, gerar altos custos para os sistemas de saúde e restringir a capacidade funcional do indivíduo interferindo de forma negativa na qualidade de vida dos pacientes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) .…”
Section: Introductionunclassified
“…De acordo com a Scottish Intercollegiate Guidelines Network, as Úlceras Venosas também denominada úlcera de estase ou varicosa, são as lesões mais graves da Síndrome da Insuficiência Venosa Crônica dos membros inferiores. A Úlcera Venosa é um problema de saúde pública por demandar cuidados contínuos, gerar altos custos para os sistemas de saúde e restringir a capacidade funcional do indivíduo interferindo de forma negativa na qualidade de vida dos pacientes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) .…”
Section: Introductionunclassified
“…As previously shown limb heaviness (72.9%), ankle swelling (68.4%), and nighttime leg cramps (58.6%) are the most frequent CVD signs reported by patients, with a difficultto-explain significant territorial diversity in the prevalence at least across Poland [23]. It seems that the prevalence of symptoms could be affected by the judgment of the cause of symptoms in patients with multimorbidity, which may be dependent on some regional differences in pre-and postgraduate training of physicians.…”
Section: Discussionmentioning
confidence: 83%
“…In a large epidemiological study conducted in 2003 in Poland, signs of CVD were reported in 47% of all women and 37% of all men [12]. In a subsequent study conducted in Poland involving 13.393 participants, initial symptoms of CVD were observed in 56.1% of all subjects [13]. The adverse socio-economic impact of CVD Current Issues in Pharmacy and Medical Sciences is particularly determined by the occurrence of venous ulcers, which significantly reduces the daily activity of patients and their quality of life [1,14].…”
Section: Microrna Expression Biomarkers Of Chronic Venous Diseasementioning
confidence: 99%